Rent Generation Under the Norwegian Rights-Based Pelagic Fishery - Bertheussen, Bernt A.; Vassdal, Terje (Frontiers in Marine Science, 2022)
As a general rule, only active fishermen can own fishing boats for commercial fishing in Norway. Thus, vertical integration is not allowed. Accordingly, the Norwegian empirical context is exceptionally well suited to study actual rent creation as a potential resource rent can only accrue to the catch stage of the value chain. This paper examines profitability and rent generation of 35 seagoing Norwegian purse seiners (around half the population) for 13 consecutive years. The study period starts in 2005, which saw the introduction of the latest version of the Norwegian individual transferable quota (ITQ) variant, or the so-called structural quota (SQ) system. First, this study investigates how profitable a purse seiner has become during the SQ regime. As per our findings, it was found that the average annual return on equity (ROE) was 20.8% and that the book value of equity more than doubled over the period (a 166% increase). Moreover, for the cohort of 35 vessels, rent operationalized as residual income (RI) was reported for every year examined (2006–2017). The discounted value of RI for the period was approximately 50 million NOK per vessel, which is equivalent to about 5 million EUR. This implies that the players generated substantial rent. The findings of this study draw a picture of a financially stable and lucrative industry. Finally, implications of the findings are discussed.